Federal Appeals Court Responses to Supreme Court Precedent. (1st November 2022) - Kassow, Benjamin J.; Fix, Michael P.
Abstract: This manuscript examines how federal appeals courts respond to precedent, in this case, Central Hudson Gas & Electric Corporation v. Public Service Commission. This account includes a comprehensive theory that examines attitudinal factors that relate to Central Hudson, specific relevant legal factors that relate to the case, as well as strategic considerations. We additionally argue that federal appeals courts may reasonably ignore Central Hudson in certain specific instances (most notably when other highly relevant cases are available for lower federal court judges to use). Our results show partial support for several portions of our theory, including a lower propensity for federal appeals courts to positively treat precedent when ideological distance is high. We also find support for one of our factual-based hypotheses (regarding cases that involve drugs and attorney advertising, where other U.S. Supreme Court precedents are readily available for appeals court judges to use).